Lignin‐derived heteroatom‐doped porous carbons for supercapacitor and CO2 capture applications. (6th April 2018) - Demir, Muslum; Tessema, Tsemre‐Dingel; Farghaly, Ahmed A.; Nyankson, Emmanuel; Saraswat, Sushil K.; Aksoy, Burak; Islamoglu, Timur; Collinson, Maryanne M.; El‐Kaderi, Hani M.; Gupta, Ram B.
Summary: The present study reports the economic and sustainable syntheses of functional porous carbons for supercapacitor and CO2 capture applications. Lignin, a byproduct of pulp and paper industry, was successfully converted into a series of heteroatom‐doped porous carbons (LHPCs) through a hydrothermal carbonization followed by a chemical activating treatment. The prepared carbons include in the range of 2.5 to 5.6 wt% nitrogen and 54 wt% oxygen in its structure. All the prepared carbons exhibit micro‐ and mesoporous structures with a high surface area in the range of 1788 to 2957 m 2 g −1 . As‐prepared LHPCs as an active electrode material and CO2 adsorbents were investigated for supercapacitor and CO2 capture applications. Lignin‐derived heteroatom‐doped porous carbon 850 shows an outstanding gravimetric specific capacitance of 372 F g −1 and excellent cyclic stability over 30, 000 cycles in 1 M KOH. Lignin‐derived heteroatom‐doped porous carbon 700 displays a remarkable CO2 capture capacity of up to 4.8 mmol g −1 (1 bar and 298 K). This study illustrates the effective transformation of a sustainable waste product into a highly functional carbon material for energy storage and CO2 separation applications. Abstract : The present work has successfully explored the potential utilization of an abundant and sustainable lignin as a precursor for heteroatom‐doped carbons in high‐performance energy storage and CO2 capture applications. As‐prepared carbon is capable of energy storage up to 372 F g −1 at 10 mV s −1 scan rate, and offer excellent CO2 adsorption capacity (at 1 bar) of 8.2 and 4.8 mmol g −1 at 273 and 298 K, respectively.